Multikulturalisme Pendidikan Agama Islam - Rantio, Gusti; Rahman, Sawaludin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This paper wants to see how the implementation of multiculturalism values ​​is developed especially in Islamic religious education. Indonesia is an archipelagic country that has diversity. This study uses a qualitative (descriptive) approach to look at situations that can save potential conflicts among the community regarding religious diversity. The results of the study, the position of religious education in the reality of multiculturalism is very real. Seeing that Islamic Religious Education with a multicultural perspective will be a learning process that pays attention to all kinds of diversity within the religion of Islam itself. Therefore, Islamic Religious Education in essence does not deny the reality of multiculturalism. In conclusion, the implementation of PAI in diversity can be done by preparing starting from planning, curriculum and materials carried out by PAI teachers must really understand multiculturalism education, the curriculum must be designed and implemented in accordance with the concept of multiculturalism, as well as the delivery of material to students must be given insight into multiculturalism. Keywords: Implementation, Multiculturalism, Islamic Religious Education